A Study into Politeness Strategies and Politeness Markers in Advertisements as Persuasive Tools - Pishghadam, Reza; Navari, Safoora (Richtmann Publishing, 2012)
This study aimed to investigate the pragmatic function of politeness in a less-talked-about communicative act:advertising. Politeness theory being discussed by Leech (1983) and being analysed by the taxonomy of Brown and Levinson(1987), is known to be as one of the essential factors for a successful communication whose success is guaranteed byappropriate persuasive tools. The major focus of this study was to explore the politeness strategies adopted in English andPersian ads and finding their persuasive factors by comparing and contrasting them. To this end, a corpus of 100 Persian andEnglish ads was collected. Their lines were first analysed to pinpoint the politeness strategy category and subcategory in bothlanguages and then their frequencies were computed. Analysis of the results based on Brown and Levinson’s (1987) taxonomyof politeness functions indicated that English ads made more use of Positive politeness strategies while in Persian ads indirectOff-record strategies were more favoured. Exploring the findings according to Nisbett’s (2004) classification of Eastern andWestern cultural system confirmed the collectivist in contrary to individualistic nature of culture in those countries respectively.Consequently, it was illustrated that the choices of psychological strategies made by advertisers to persuade customers were inline with their intended culture.